Mało znane źródło germanizmów: wileński Słownik błędów językowych Juliana Szweda - Cieszkowski, Marek; Mędelska, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The dictionary mentioned in the title was compiled in the interwar period (1918- -1939) and was then quite well known. Today, very few people remember about it. In the opinion of the authors of the article, it is worthwhile to remind about this book, especially to the scholars studying foreign influences upon the Polish language, including— which may seem surprising—the linguists investigating the influence of the German language upon the Polish language. In his guide, J. Szwed used not only the linguistic material collected in the Vilnius province, he had strong personal ties with, but also originating from Little Poland and Cieszyn Silesia. As it has been shown in the analysis, there were more than 180 lexical Germanisms in the small dictionary from Vilnius, i.e., definitely more than in the other publications of this type issued in the first half of the 20th century. This material is dominated by loan words, quite well known in the Polish language (130 items), recorded in 1-2 definition dictionaries, e.g., cug “train”, fojt “voivode”. However, we also find the Germanisms that are evidenced only in the small dictionary by J. Szwed, for instance bruch “hernia”. In the publication of the Vilnius teacher we can also find phonetic Germanisms (e.g., voiced s after sonorous consonants in foreign words, comp.: intenzywny, konzul), inflectional (e.g., changes of grammatical gender) and syntactical (e.g., mam pieniądze na banku [I have got money on the bank], instead of: w banku [in the bank]).